The Role of Jet Adjustment Processes in Subtropical Dust Storms. Issue 22 (20th November 2017) - Pokharel, Ashok Kumar; Kaplan, Michael L.; Fiedler, Stephanie
Abstract: Meso‐α/β/γ scale atmospheric processes of jet dynamics responsible for generating Harmattan, Saudi Arabian, and Bodélé Depression dust storms are analyzed with observations and high‐resolution modeling. The analysis of the role of jet adjustment processes in each dust storm shows similarities as follows: (1) the presence of a well‐organized baroclinic synoptic scale system, (2) cross mountain flows that produced a leeside inversion layer prior to the large‐scale dust storm, (3) the presence of thermal wind imbalance in the exit region of the midtropospheric jet streak in the lee of the respective mountains shortly after the time of the inversion formation, (4) dust storm formation accompanied by large magnitude ageostrophic isallobaric low‐level winds as part of the meso‐β scale adjustment process, (5) substantial low‐level turbulence kinetic energy (TKE), and (6) emission and uplift of mineral dust in the lee of nearby mountains. The thermally forced meso‐γ scale adjustment processes, which occurred in the canyons/small valleys, may have been the cause of numerous observed dust streaks leading to the entry of the dust into the atmosphere due to the presence of significant vertical motion and TKE generation. This study points to the importance of meso‐β to meso‐γ scale adjustment processes at low atmospheric levels due to an imbalance within the exit region of an upper level jet streak for the formation of severe dust storms. The low level TKE, which is one of the prerequisites to deflate the dust from the surface, cannot be detected with the low resolution data sets; so our results show that a high spatial resolution is required for better representing TKE as a proxy for dust emission. Key Points: Thermal wind imbalance in the exit region of the jet streak resulted in a mesoscale jetlet in the lee of the mountains Thermally direct transverse ageostrophic circulation in the exit region of the jetlet led to the upward motion and adiabatic expansion Low‐level pressure rise generated the ageostrophic isallobaric wind that advected cold air toward the thermally induced low pressure area